Students as co-researchers to inform student learning: Findings from a poverty simulation. Issue 2 (June 2020) - Roll, Susan; Browne, Laurie
Survey data reveal that poverty simulations are an effective tool in changing student attitudes about poverty. What is not well documented in the literature is exactly how students learn through this type of experiential education. Using students as co-researchers in an action research model, this study sought to better understand how students learn about poverty through a poverty simulation, which is a pedagogical tool known to impact students' attitudes and understandings of poverty. Results map closely with transformational learning theory, including that personal background and previous learning experiences shaped students openness and willingness to engage in a new learning opportunity. Students reflected how the climate of the learning environment, in this case the poverty simulation, was as a significant factor that impacted the learning process. Finally, findings from this study indicate that students had both an increased interest in issues of social justice and felt less judgmental of people experiencing poverty following the simulation. Additionally, the student research team itself had a learning opportunity which resulted in an increased interest and appreciation for participatory research.